THE IMPORTANCE AND USE OF KEY PERFORMANCE INDICATORS OF KNOWLEDGE MANAGEMENT IN QUANTITY SURVEYING FIRMS IN NIGERIA. - Adegbembo, Taiwo (Journal of Surveying, Construction and Property, 2022)
Quantity surveying firms in Nigeria are performing poorly and Knowledge Management (KM) has been identified as crucial to the survival of organisations, so measuring the KM of a firm is fundamental to the success of KM and the firm at large. Therefore, the study aims to assess the Key Performance Indicators (KPIs) for measuring KM in Quantity Surveying Firms (QSFs) with a view to ascertain the KPI important and used by QSFs in Nigeria. The study adopted the survey research design where quantitative data was collected through the use of a structured questionnaire on a 5 Likert scale. Descriptive and inferential statistics were used to analyse the data collected and the result discussed. A total of 86 questionnaires were retrieved out of the 134 distributed making the response rate 64% and all were deemed fit for analysis. The reliability of the questionnaire was tested and the Cronbach Alpha test gave a value of 0.888 which makes the data fit for analysis. Mean Item Score (MIS) was used to rank the factors while quadrant analysis was used to compare the rate of importance with the rate of use of the identified KPI. Findings indicate that both usefulness of stored knowledge and knowledge exchange that led to innovation was the most important and used performance indicators in QSFs while distributed incentives, classifications in databases, and other contributions are the least important and used by QSFs. This implies that QSFs reuse the knowledge stored in their databases as they find the knowledge stored very useful. Also, the firms make use of the knowledge they acquire from each other to develop innovations within the organisation.